A generic data driven approach for low sampling load disaggregation. (March 2017) - Basu, Kaustav; Debusschere, Vincent; Bacha, Seddik; Hably, Ahmad; Van Delft, Danny; Jan Dirven, Geert
Abstract: Non-intrusive load monitoring (Nilm ) deals with the disaggregation of individual appliances from the total reading at the power meter. This work proposes an industrial scale solution which uses a specific modeling technique for appliance detection, trained and tested on two distinct databases extracted from actual customers readings. The proposed method is tested for different household categories to address its robustness. The validation of the implemented solution is done over a period of one month with a sampling rate of 10 s. The results indicate that high energy consuming appliance can be correctly detected ( > 80% of accuracy). In addition, general cases of errors are analyzed, paving the way of the next step in the development of a commercial application of the proposed method.